Acute and subchronic toxicity evaluation of methanol stem-bark extract of Ximenia americana Linn (Olacaceae) in Wistar rats - Isaac A. Agyigra; Jane I. Ejiofor; Mohammed G. Magaji (Faculty of Pharmacy, Cairo University, 2017)
Ximenia americana is used in African ethno-medicine for spasmodic bowel diseases with stem bark particularly used for ulcers. This study evaluated the toxicity-profile of methanol stem-bark extract. Extract doses were selected from estimated oral median lethal dose (LD50) of acute toxicity test. Ten male Wistar rats in 4-groups, weekly weighed and daily treated orally per body-weight for 28Â days with normal-saline and extract-doses (250, 500, 1000Â mg/kg) respectively were euthanized. Blood for biochemical and haematological analyses were collected into plain and anticoagulated (EDTA) sample-bottles respectively from each group. Vital-organs were isolated, weighed and fixed in buffered-formalin fixatives for histo-analyses. MeanÂ Â±Â standard-error of mean and statistical-significance at (pÂ â¤Â 0.05) of obtained-data were evaluated. The extract at up to 5000Â mg/kg caused no mortality or behavioural toxic-signs and thus, oral LD50 was estimated to be greater than 5000Â mg/kg. No changes in organ-sizes, body-weights or anatomy of brain, heart, liver and stomach occurred, but at 1000Â mg/kg, kidney showed vascular-congestion with polymorphonuclear cells, lungs had consolidated areas of polymorphs infiltration, while spleen had distorted germinal-centres. Liver enzymes and urea levels were not altered significantly, but a dose dependent significant increase in total-protein only at 1000Â mg/kg; and significant reduction in albumin level at 500 and 1000Â mg/kg were observed. The observed dose-dependent reduction in creatinine was not significant. Total-calcium and chloride ion concentrations increased significantly only at 250Â mg/kg. In conclusion, acute oral administration of methanol stem-bark extract of Ximenia americana was relatively non-toxic in mice, but minimal anatomical changes in kidney, lungs and spleen occurred when used for few weeks in rats. Keywords: Ximenia americana, Stem-bark, Methanol extract, Toxicity profile